Effect of gadolinium concentration on temperature change under magnetic field. - Kemal Arda; Sinan Akay; Cevat Erisken (PLoS ONE, 2019)
Gadolinium based contrast agents (GBCAs) were found to play a role in nephrogenic systemic fibrosis in patients with and without renal impairment. Therefore, preserving the structural stability of GBCAs to reduce their propensity to liberate Gd3+ is of utmost importance. This study evaluates the effect of gadolinium concentration of GBCAs on solution temperature under magnetic fields. It is hypothesized that presence of gadolinium will lead to temperature changes of its solutions under magnetic field, and this change will depend on concentration. In this study, GBCAs were diluted to concentrations of 0.6, 1.2, 1.8, 2.4 mMol/L. A 10mL preparation in pure water, simulated body fluid (SBF), and plasma was scanned at 3T following a soft tissue neck protocol, and their temperatures were measured. Findings revealed that concentration of GBCA had significant effect on temperature change in all dilution media. Type of commercially available GBCA had an effect only in SFB and plasma. Evaluation of correlation between conditional stability constant (Kcond) and temperature difference (ΔT) revealed that in water and SBF there exists a positive correlation between Kcond and temperature variation. Collectively, GBCAs can cause local temperature variations when administered into patients, and can affect dissociation of gadolinium from its chelates, which should be investigated in a further study.